(untitled) - Hart, Carolyn G. (New York, 2013)
"Bailey Ruth loves to return to earth as an emissary from Heaven's Department of Good Intentions. Problem is, she's a bit of a loose cannon as far as ghosts go--forgetting to remain invisible, alarming earthly creatures--so she's far from the top of department head Wiggins's go-to list for assignments. That's why she's surprised when the Heaven-sent Rescue Express drops her off at a frame house on the outskirts of her old hometown, Adelaide, Oklahoma, where a young man is playing the drums. What kind of rescuing does he need--drum lessons? But when a window cracks and a rifle barrel is thrust inside, only Bailey Ruth's hasty intervention saves Nick Magruder from taking a bullet. When she materializes to reassure him, she finds she can't go back to vanishing. What gives? It turns out she's been tricked by Nick's late aunt--Delilah Delahunt Duvall--to come to the young man's rescue, which means she isn't back on earth in service of the department. Wiggins has no idea where she is--and now she may be trapped in Adelaide forever. Unless she can help Aunt Dee snare the person who wants her nephew dead."--
Kirkus Reviews
Publishers Weekly
Adult.
Adult.
Keywords: Mystery fiction; Ghost stories; Humorous fiction; Spirits; Fiction; Criminal investigation; Fiction; Homicide; Fiction; Oklahoma; Fiction